Front Cover: Lewis Superacidic Tellurenyl Cation‐Induced Electrophilic Activation of an Inert Carborane (Chem. Eur. J. 59/2021). Issue 59 (8th October 2021) - Hejda, Martin; Duvinage, Daniel; Lork, Enno; Lyčka, Antonín; Černošek, Zdeněk; Macháček, Jan; Makarov, Sergey; Ketkov, Sergey; Mebs, Stefan; Dostál, Libor; Beckmann, Jens
Abstract : In a metastable N‐coordinated Lewis superacidic tellurenyl cation–carborane ion pair, the Te atom is trying to steal the H atom with help of a N atom. However, although at first glance the N atom is helping, he is actually planning to steal the asset for himself. The Town Musicians came to scare off the robbers, but they arrived too late, and thus nothing can stop nitrogen's plan. The broken window opens full insight into the electrophilic activation mechanism of the carborane moiety, which has been poorly understood so far. Elemental Te is watching the whole show and wondering how this is even possible; but was it the Te atom that broke the window? More information can be found in the Communication by M. Hejda, S. Ketkov, S. Mebs, J. Beckmann, et al. (DOI: 10.1002/chem.202103181 ).